ANALISIS WACANA PRAGMATIK TINDAK TUTUR DAN DAN IMPLIKATUR DALAM RUBIK POS PEMBACA PADA HARIAN SOLOPOS EDISI 20 NOVEMBER 2025 - Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the forms of locutionary, illocutionary, perlocutionary, and implicature speech acts in the "Readers' Letter" section of the Solopos Daily Newspaper. Data collection used non-participant observation with note-taking techniques. Data analysis employed referential, distributional, introspective-reflexive, and abductive inference techniques. The results of the discussion indicate that metaphors in the readers' letters contain pragmatic functions such as assertive, directive, and expressive. The pragmatic functions found indicate the indirectness of intent in metaphorical expressions. This indirectness of intent indicates a politeness strategy used by the readers' letters writers to maintain a good relationship with the readers. The readers' letters writers give the readers the freedom to agree or disagree with the discourse presented. Keywords: locutionary speech acts, illocutionary, perlocutionary, implicature